1977
DOI: 10.1093/oxfordjournals.aje.a112470
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Epstein-Barr Virus Capsid Antigen and Early Antigen in Nasopharyngeal Carcinoma and Comparison Groups

Abstract: Antibodies to Epstein-Barr virus capsid antigen (anti-VCA) and early antigen (anti-EA) were measured in 263 patients with nasopharyngeal carcinoma (NPC), 624 age- and sex-matched neighborhood controls, 570 family members of NPC patients and 830 family members of neighborhood controls in Taiwan. The distribution of antibody titers was significantly different between NPC patients and the other three groups. More than 55% and 45% of NPC patients had titers of greater than or equal to 1:640 and greater than or equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1979
1979
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…This finding was confirmed in 1970, when anti-EBV antibodies were observed to be higher in NPC patients than in controls (61). Subsequent studies showed that NPC patients have elevated IgG and IgA antibody titers to the EBV viral capsid antigen lgA and early antigen, as well as increased IgG against the latent viral nuclear antigens 1 and 2 (EBNA-1, EBNA-2) and neutralizing antibodies against EBV-specific DNase (62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74). Moreover, these antibody titers, especially of IgA, precede tumor development by several years (75) and are correlated with tumor burden, remission, and recurrence (76)(77)(78)(79)(80)(81)(82)(83)(84).…”
Section: Risk Factorsmentioning
confidence: 99%
“…This finding was confirmed in 1970, when anti-EBV antibodies were observed to be higher in NPC patients than in controls (61). Subsequent studies showed that NPC patients have elevated IgG and IgA antibody titers to the EBV viral capsid antigen lgA and early antigen, as well as increased IgG against the latent viral nuclear antigens 1 and 2 (EBNA-1, EBNA-2) and neutralizing antibodies against EBV-specific DNase (62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74). Moreover, these antibody titers, especially of IgA, precede tumor development by several years (75) and are correlated with tumor burden, remission, and recurrence (76)(77)(78)(79)(80)(81)(82)(83)(84).…”
Section: Risk Factorsmentioning
confidence: 99%
“…22 Briefly, all solutions and reagents were (PTCL). 16,17 However, the incidence of BL in Taiwan is prepared with water treated with dietholpyrocarbonate. Ten micrometer sections cut from paraffin rare.…”
Section: Greater Than 90% Of the Population In Taiwan Hasmentioning
confidence: 99%
“…Several studies have investigated EBV antibodies in human serum as potential NPC biomarkers in case/control (7)(8)(9)(10) and prospective studies (11)(12)(13), including IgA antibodies against the EBV viral capsid antigen (VCA), early antigen (EA), and EBV nuclear antigen 1 (EBNA1) measured via immunofluorescence assay (IFA) or enzyme-linked immunosorbent assay (ELISA). Other EBV antigens from the roughly 100 protein-coding open reading frames and other antibody isotypes (especially IgG) have been examined less frequently.…”
mentioning
confidence: 99%